(untitled) (Jurnal Teknologi Industri Pertanian, 2017)
Deterioration of bleachability index (DOBI) is one of the parameters in the refining process, to meet the quality of commercial crude palm oil (CPO); Miixing between high quality CPO and low quality CPO sometimes were undertaken. This study was conducted to assess the effect of dose of bleaching earth (BE) and time of bleaching process of various CPO quality, especially CPOs that had different DOBIs. The raw materials used were CPO with DOBIs of 0.65 to 4.80 which obtained from different raw materials, namely of fresh fruit bunches (FFB), palm oil mill (POM), waste from POM, and CPO from FFB heated at 120°C (during 30 and 60 minutes) and mixed with low quality CPO (ratio of 6:4 and 1:9). CPOs were bleached using BE doses of 0.5%, 1.0%, 2.5%, and 2% and time for 15, 30, 45, and 60 minutes. The results obtained from preparation of raw materials were CPO with DOBI of 3.9 and 4.8 (CPO from FFB 1 and 2), 1.4 and 2.68 (CPO from POM 1 and 2) and 0.85 (CPO from waste POM 2) as well as 2.5 and 0.65 (heating) and 2.92 and 1.52 (mixing). The warming of CPO caused colour, carotene, and water content decreased, while free fatty acids (FFA) and peroxide value (PV) increased. The more CPO low quality mixed to CPO high quality caused carotene and DOBI decreased while colour, moisture content, FFB, and PV increased. The results of bleaching showed that increasing time and dose of BE caused colour, carotene, DOBI, and water contents decreased, while FFA increased. PV decreased with increasing doses of BE and for 30 minutes PV decreased then increased with increasing time. Bleaching process of CPO from mixing between high quality CPO and low quality CPO might increase FFA, despite the mixture resulted CPO had high DOBI. This would impact on the deodorization process. Keywords: crude palm oil, bleaching, bleaching earth, deterioration of bleachability index